Problematics of approaches to research of the use safety of ergatic control systems on railway transport - Kamenyev, O. Y. (Science and Transport Progress, 2013)
Purpose. Determination of the protective state influence of ergatic control system on a railway transport on their use safety. Making recommendations concerning its accounting for regulations and testing during the development and implementation. Methodology. Research is executed on the base of reliability theory with the use of exponential law of refusals distribution. Findings. It is shown that confirmation of ergatic technical control facilities accordance and trains traffic arrangement to certain functional level of security is not sufficient for guaranteeing of their use safety. It is established that the protective refusal of ergatic control system does not exclude, but only postpones the dangerous condition of the system. Originality. Further development of approach and requirements to research of use safety of ergatic control system on a railway transport are received. Unlike previous they take into account the indexes of not only functional unconcern, but also faultlessness at setting of norms and proof of these systems safety. Practical value. Accounting of protective refusals of technical facilities at tests on their safety application, and also setting of norms of characteristics reliability of control systems by responsible technological processes on a railway transport in accordance with offered approach allows to increase level of their use safety in the exploitation process.